2020
DOI: 10.1002/ccd.28980
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography predictors of target vessel myocardial infarction after provisional stenting in patients with coronary bifurcation disease

Abstract: Background Provisional side branch (SB) stenting is correlated with target vessel myocardial infarction (TVMI) in patients with coronary bifurcation lesions. However, the mechanisms underlying this association remain unknown. Objectives To determine the correlation between SB lesion length with vulnerable plaques and TVMI using optical coherence tomography (OCT). Background The correlation between SB lesion length with vulnerable plaques and TVMI is unknown. Methods A total of 405 patients with 405 bifurcation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In the recent DEFINITION II trial, 17 the prevalence of PMI according to the DEFINITION criteria 14 was 5.8% after provisional stenting, thereby indicating a strong relationship between complex bifurcations, stenting techniques, and PMI. Those results all linked the SB lesions length to the occurrence of PMI, supported by a recent study, 23 which reported that patients with a longer SB lesion length had more frequent vulnerable plaques around bifurcation area.…”
Section: Discussionsupporting
confidence: 74%
“…In the recent DEFINITION II trial, 17 the prevalence of PMI according to the DEFINITION criteria 14 was 5.8% after provisional stenting, thereby indicating a strong relationship between complex bifurcations, stenting techniques, and PMI. Those results all linked the SB lesions length to the occurrence of PMI, supported by a recent study, 23 which reported that patients with a longer SB lesion length had more frequent vulnerable plaques around bifurcation area.…”
Section: Discussionsupporting
confidence: 74%
“…At 1-year follow-up after PS, there were 31 (7.7%) TVMI, of which 21 (11.8%) were found in the long SB lesion group and 10 (4.4%) were found in the short SB lesion group (p=0.009). Using multivariate regression analysis, it was shown that a long SB lesion length (p=0.011), the absence of vulnerable plaques in the polygon of confluence (p=0.001), and true coronary bifurcation lesions (p=0.004) were the 3 independent factors of TVMI 26 . Coronary bifurcation lesions with a longer SB lesion length are definitively associated with more frequent vulnerable disease, leading to increased TVMI rates, and this finding is consistent with reports by the DEFINITION II trial.…”
Section: Why Do Definition Criteria-defined Bifurcation Lesions Incre...mentioning
confidence: 99%
“…The rate of spontaneous MI is comparable between PS and a two-stent approach [12][13][14][15][16][17] ; however, the rate of PMI was significantly higher in the PS arm of the DKCRUSH V 13 and DEFINITION II 12 trials. In a total of 405 patients with 405 bifurcation lesions who underwent preprocedural OCT imaging of both the main vessel (MV) and the SB 18 , vulnerable plaques were predominantly localised in the MV and were more frequently in the long SB (≥10 mm) lesion group (42.7%) than in the short SB lesion group (24.2%, p<0.001). At one-year follow-up after provisional stenting, there were 31 (7.7%) TVMIs, with 21 (11.8%) in the long SB lesion group and 10 (4.4%) in the short SB lesion group (p=0.009).…”
Section: Is the Complexity Of Lm Bifurcations Influencing Clinical Outcome After Pci?mentioning
confidence: 99%